2002
DOI: 10.1596/1813-9450-2924
|View full text |Cite
|
Sign up to set email alerts
|

Financial Development, Property Rights, and Growth

Abstract: Claessens and Laeven analyze how property rights affectThe authors find that improved asset allocation due to the allocation of firms' available resources among better property rights has an effect on growth in sectoral different types of assets. In particular, they investigate value added equal to improved access to financing arising empirically for a large number of countries whether firms from greater financial development. The results are in environments with more secure property rights robust, using vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
323
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(340 citation statements)
references
References 16 publications
14
323
0
3
Order By: Relevance
“…Meanwhile, not surprisingly, it has been shown that weak property rights protection increases the perception of risk for would be entrepreneurs, deters individuals from starting up a business and reduces their involvement in future development projects (Besley, 1995;Frye and Shleifer, 1997;La Porta et al, 1997;Demirgüç-Kunt and Vojislav, 1998;Johnson et al, 2002;Kumar et al, 2002;Claessens and Laeven, 2003). Fears over poor property protection rights tend to stifle the creation of businesses.…”
Section: Business Creation and Institutional Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, not surprisingly, it has been shown that weak property rights protection increases the perception of risk for would be entrepreneurs, deters individuals from starting up a business and reduces their involvement in future development projects (Besley, 1995;Frye and Shleifer, 1997;La Porta et al, 1997;Demirgüç-Kunt and Vojislav, 1998;Johnson et al, 2002;Kumar et al, 2002;Claessens and Laeven, 2003). Fears over poor property protection rights tend to stifle the creation of businesses.…”
Section: Business Creation and Institutional Qualitymentioning
confidence: 99%
“…These indicators are designed so that together they measure the main aspects of a free market in a country by reference to how the players respond to changing market conditions. Other studies that used this methodology using IEF indicators are (Claessens and Laeven, 2003;Klapper et al, 2006;McMullen et al, 2008;Aidis et al, 2010;Doucouliagos and Ulubasoglu, 2006;Heckelman, 2000;Han and Sturm, 2000).…”
Section: Free Markets and Foreign Direct Investmentmentioning
confidence: 99%
“…In the first instance, there is of course the large background literature relating good institutions positively to financial sector development (Demirgüç-Kunt and Levine 1996;Claessens and Laeven 2003), in that good institutions help support the growth of the financial sector more broadly. There also already exists a wealth of research on institutional development in 1 Moreover, Fang et al (2014) do not include CIS countries in their dataset, which I do here.…”
Section: Bank Profitability In Transition: the Role Of Institutionsmentioning
confidence: 99%
“…5 Claessens and Laeven (2003) show that the security of property rights has as large an effect on asset allocation and firm growth as financial development does. Lack of property rights induce firms to over-invest in tangible capital which is easier to protect from competitors.…”
Section: How Do Banks Intermediate Foreign Direct Investment?mentioning
confidence: 99%